Treatment patterns in patients with type 2 diabetes mellitus treated with glucagon‐like peptide‐1 receptor agonists: Higher adherence and persistence with dulaglutide compared with once‐weekly exenatide and liraglutide. Issue 7 (16th March 2017) - Alatorre, Carlos; Fernández Landó, Laura; Yu, Maria; Brown, Katelyn; Montejano, Leslie; Juneau, Paul; Mody, Reema; Swindle, Ralph
Abstract : Aims: To compare adherence (proportion of days covered [PDC]), persistence, and treatment patterns among patients with type 2 diabetes mellitus (T2DM) newly initiating glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs). More specifically, the main objectives were to compare dulaglutide vs exenatide once weekly and dulaglutide vs liraglutide. Methods: Patients with T2DM newly initiating dulaglutide, albiglutide, exenatide once weekly, exenatide twice daily and liraglutide between November 2014 and April 2015 were hierarchically selected from Truven Health's MarketScan Research Databases. Propensity score matching was used to account for selection bias. Adherence to and persistence with the index GLP‐1RA, and switching and augmentation patterns were assessed during the 6‐month post‐index period. Results: Mean adherence for the matched cohorts was significantly higher for dulaglutide than for exenatide once weekly (0.72 vs 0.61; P  < .0001) and liraglutide (0.71 vs 0.67; P  < .0001). The percentage of patients achieving PDC ≥ 0.80 was significantly higher for dulaglutide compared with exenatide once weekly (54.2% vs 37.9%; P  < .0001) and liraglutide (53.5% vs 44.3%; P  < .0001). The mean (standard deviation) days on treatment for all matched patients was significantly higher for patients in the dulaglutide cohort compared with those in the exenatide once‐weekly (148.4 [55.4] vs 123.6 [61.6]; P  < .0001) and liraglutide cohorts (146.0 [56.9] vs 137.4 [60.1]; P  < .0001). A significantly lower proportion of patients on dulaglutide discontinued treatment compared with those on exenatide once weekly (26.2% vs 48.4%; P  < .0001) and those on liraglutide (28.0% vs 35.6%; P  < .0001). Conclusions: Dulaglutide initiators had significantly higher adherence, were more persistent, and had lower discontinuation rates compared with initiators of exenatide once weekly or liraglutide during the 6‐month follow‐up period.